2009
DOI: 10.4161/cbt.8.10.8149
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological analyses of the antitumor activity of anti-glypican-3 antibody (GC33) in human liver cancer xenograft models: The essential role of macrophages

Abstract: Previously, we demonstrated the antitumor efficacy of the antiglypican-3 (GPC3) antibody GC33 in several human liver cancer xenograft models and the important role of antibody-dependent cellular cytotoxicity (ADCC) in the antitumor mechanism of GC33. Involvement of other mechanisms such as modulation of the functions of GPC3 in antitumor activity remains to be elucidated. In this study, we investigated histopathologically time-course changes in xenografts in mice following a single administration of GC33 to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Expression on the cell surface makes GPC3 an attractive target for antibody-directed therapy. Another group has shown that a murine anti-hGPC3 antibody induces antibody-dependent cytotoxicity that manifests an anti-tumor effect in a xenograft animal model of hepatocellular carcinoma [31]; this antibody has subsequently been humanized [18] and is entering human clinical trials. Thus, available evidence suggests that glypican-3 is a rational target for humoral and potentially chimeric immunotherapy for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Expression on the cell surface makes GPC3 an attractive target for antibody-directed therapy. Another group has shown that a murine anti-hGPC3 antibody induces antibody-dependent cytotoxicity that manifests an anti-tumor effect in a xenograft animal model of hepatocellular carcinoma [31]; this antibody has subsequently been humanized [18] and is entering human clinical trials. Thus, available evidence suggests that glypican-3 is a rational target for humoral and potentially chimeric immunotherapy for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…By using human peripheral blood mononuclear cells (PBMCs) depleted of either CD56+ or CD14+ cells, they show that the ADCC is carried out primarily by CD56 + natural killer cells, while additional studies suggest tumor-associated macrophages play a role in the antitumor effect [40]. They show tumor infiltration by macrophages, but also consider mechanisms other than ADCC such as GPC3 modulation.…”
Section: Glypican 3 Targeted Therapy; Antibody-based Approachmentioning
confidence: 99%
“…Based on these evidences, they observed the involvements of infiltrated TAM in anti-GPC3 immunotherapy model using GC33, showing macrophages may play an important role in the anti-tumor activity of GC33 by non-ADCC mechanisms such as modulation of GPC3 functions 45. In addition, GC33 does not directly inhibit the proliferation of GPC3-positive tumor cells 45. To fully evaluate GPC3-targeted antibody therapy, the mAbs that target different functional domains (including the HS chain) of GPC3 would be useful.…”
Section: Gpc3-targeted Immunotherapymentioning
confidence: 99%
“…investigated the relationship between membrane expression of GPC3 and recruitment of tumor-associated macrophage (TAM) 43,44. Based on these evidences, they observed the involvements of infiltrated TAM in anti-GPC3 immunotherapy model using GC33, showing macrophages may play an important role in the anti-tumor activity of GC33 by non-ADCC mechanisms such as modulation of GPC3 functions 45. In addition, GC33 does not directly inhibit the proliferation of GPC3-positive tumor cells 45.…”
Section: Gpc3-targeted Immunotherapymentioning
confidence: 99%